Methane emissions from the East Siberian Arctic Shelf inferred from accurate observations of atmospheric methane mole fractions - Reum, Friedemann (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2019)
In the Arctic, vast carbon reservoirs are preserved by cold climate conditions. Due to climate change, they are at risk of degradation, which could lead to increased levels of greenhouse gases in the atmosphere. One of these reservoirs is the seabed of the East Siberian Arctic Shelf (ESAS), which has in recent years attracted attention as a potentially large source of methane (CH4) to the atmosphere, both at present and in warmer conditions projected by climate models for the coming decades. Yet, estimates of the current annual CH4 outgassing of the shelf as well as key controls of the emissions are highly uncertain. One reason for the uncertainties is limited data coverage. Thus, this work aims at (1) improving the data availability on CH4 emissions from the East Siberian Arctic Shelf and (2) estimating current CH4 emissions from this region to the atmosphere. To achieve the first goal, an observation station for atmospheric greenhouse gases was established in the remote locality Ambarchik at the coast of the East Siberian Sea. The station Ambarchik operates continuously since it was established in August 2014 and provides accurate CO2 and CH4 data suitable for estimating the sources and sinks of these gases via inverse modeling of atmospheric transport. As a side product of the calibration efforts of Ambarchik data, an improvement of the accuracy of measurements of greenhouse gas mole fractions in humid air with the widely used instruments manufactured by Picarro, Inc. was achieved. To achieve the second goal, data obtained at Ambarchik were used together with data from other sites to estimate CH4 emissions from the ESAS to the atmosphere via an inverse model of atmospheric CH4 transport. Results indicate that the ESAS CH4 emission budget is on the low end of literature estimates (0.4–1.5 Tg CH4/yr compared to 0–17 Tg; 1 Tg = 1e12 g). Retrieved spatial emission patterns indicate emissions originate predominantly from shallow areas of the ESAS. Seasonal variations indicate potentially large emissions during ...